Intenção empreendedora em estudantes de administração: um estudo com discentes da Universidade Federal do Ceará - Rodrigues, Ingrid Lustosa (2017)
The present work intends to identify the levels of entrepreneurial intention of Universidade Federal do Ceará’s Management students and as specific objectives to present the evolution of the concept of entrepreneurship and entrepreneurial education, to apply a questionnaire based on the model already presented by GUESSS identifying the level of entrepreneurial intent in university students and comparing the results obtained with UFC students with the GUESSS’s national average results that uses the principles of the Theory of Planned Behavior (TCP) as pillars for its characterization. The methodology for research was the quantitative approach. For primary data collection, a field survey was performed with a pre-established questionnaire, available on an online platform. With the analysis of the results it was possible to affirm that the Administration students of the Universidade Federal do Ceará have a high intention to undertake in business at some point in life. Despite this, students indicate that the University can improve in some aspects of teaching to promote university entrepreneurship.